Prevalence of endothelial dysfunction in acquired immune deficiency syndrome patients and its correlation with degree of immunodeficiency - Varte, Zorinsangi; P., Naveen; Ralte, Wendy L. (International Journal of Advances in Medicine, 2019)
Background: Number of factors play a role in endothelial dysfunction observed in AIDS patients, which can lead to atherosclerosis along with cardiovascular mortality and morbidity. Human immunodeficiency virus (HIV), the etiologic agent of AIDS causes several vascular disorders characterized by an evident activation and perturbation of endothelial cells. Currently, there is lack of data in the Indian literature regarding study of endothelial dysfunction in HIV patients. The purpose of our research was to study the prevalence of endothelial dysfunction in HIV/AIDS patients. Methods: The study comprises a total number of 60 adult HIV positive patients of both sex (male and female) with confirmed HIV seropositivity. The patients were divided into two groups of 30 each, depending on the degree of immune dysfunction (CD 4 cell counts). Group I- patients with CD 4+T cell count>200/µl and group II-patients with CD 4+T cell count<200/µl. These patients were subjected to detailed clinical examination and markers of endothelial dysfunction-flow mediated vasodilatation (FMD) of brachial artery, S. nitrite and C-reactive protein (CRP) were performed. Results: The defect in endothelial function was most prevalent in patients with more severe immunosuppression. FMD of brachial artery was decreased in patients with CD 4+T cell count < 200/µl (7.07±2.89, p=0.00). S. nitrite was also significantly lower in group II patients (26.43±15.38), and these patients also showed more CRP positivity and higher CRP titres ranging from 1.2 mg/dl to 9.6 mg/dl. Conclusions: The defect in endothelial function was most prevalent in patients with more severe immunosuppression. FMD of brachial artery was decreased in patients with CD 4+T cell count <200/µl (7.07±2.89, p=0.00). S. nitrite was also significantly lower in group II patients (26.43±15.38), and these patients also showed more CRP positivity and higher CRP titres ranging from 1.2 mg/dl to 9.6 mg/dl.